ROS and COVID - Periklis Vardakas; Zoi Skaperda; Fotios Tekos; Demetrios Kouretas (MDPI AG, 2022)
In recent years, the pandemic of coronavirus disease 19 (COVID-19), an infectious disease caused by variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has indisputably emerged as the predominant public health issue [...]